Peripheral Blood-Derived Mesenchymal Stem Cells Modulate Macrophage Plasticity through the IL-10/STAT3 Pathway - Qi-Ming Pang; Rui Yang; Meng Zhang; Wang-Hui Zou; Nan-Nan Qian; Qi-Jing Xu; Hui Chen; Jia-Chen Peng; Xiao-Ping Luo; Qian Zhang; Tao Zhang (Stem Cells International)
Mesenchymal stem cells (MSCs) are multipotent cells that can skew the balance of M1/M2 macrophage polarization towards the M2 phenotype via their paracrine effects, thereby promoting anatomical and functional recovery after many inflammatory diseases induced by macrophages. However, the underlying mechanism is still poorly understood. This study focused on the IL-10/STAT3 pathway and investigated whether IL-10 secreted by PBMSCs could mediate M2 polarization through the activation of this pathway. In this study, a Transwell system was used for coculturing macrophages and PBMSCs. ELISA and RT-qPCR analysis found that PBMSCs and their conditioned media (P-CM) significantly induced the expression of IL-10, while significantly inhibiting the expression of IL-1β and TNF-α; moreover, this effect could be reversed by adding Ab9969 (an IL-10 neutralizing antibody) and Stattic (a STAT3 inhibitor). Furthermore, western blotting and immunofluorescence assays demonstrated that JAK1/STAT3 signaling was significantly upregulated in macrophages cocultured with PBMSCs or P-CM, accompanied by an increase in the M2 biomarker CD206 and a decrease in the M1 biomarker CD86. This effect could also be reversed by blocking the IL-10/STAT3 pathway with Ab9969 and Stattic. In summary, PBMSCs could mediate the polarization of M2 macrophages by activating the IL-10/STAT3 pathway.